Internet of Things- (IoT-) Based Real-Time Vital Physiological Parameter Monitoring System for Remote Asthma Patients. (11th March 2022) - Islam, Khairul; Alam, Farabi; Zahid, Abid Ibna; Khan, Mohammad Monirujjaman; InamAbbasi, Muhammad
Abstract : In this paper, the design and implementation of an asthma patient monitoring system are presented. It can be categorized as an IoT-based device which can monitor heart rate, room temperature, humidity, air quality, nostril temperature, and oxygen saturation (SpO2 ) using an ESP8266 microcontroller and different sensors. All data will be sent to Firebase via Wi-Fi and then to patients and doctors via mobile applications and websites, respectively. Doctors can access this data via a website and instruct patients based on their specific needs. An ESP8266 microcontroller, a DHT11 temperature and humidity sensor, a MAX30100 pulse and SpO2 sensor, a MQ-135 air quality sensor, and an LM-35 temperature sensor have been used for the proposed system in this research. This system uses an efficient way to store all the data and information about the patient. It also carries their various test reports. The data is preserved in a proper way, which will help the patient or doctor retrieve any information in a smooth and swift manner. The software part of the system is divided into two parts. One of them is a mobile application that was designed by the Android Studio. The second one is the website, and it is also divided into two parts. HTML (hypertext markup language), CSS (cascading style sheets), and JavaScripts are designed for the front end of the website, and PHP (hypertext preprocessor) is used for the backend of the website. The device is tested on seven different real human test subjects, and the accuracy of that device is state of the art. It can measure the heart rate of a person along with their oxygen saturation with accuracy. Also, this device calculates the humidity properly as it changes the moment wet towels are put near the sensors and far from the sensors. It also shows the proper air quality as it has been tested with smoke to measure the extreme difference in the air quality. This system also has video calling and prescription features. Using this system, patients can consult with the doctor and get a prescription. Using this system, the vital physiological parameters of the remote patients can be measured and monitored. Any hospital or diagnostic center can be more efficient and organized by using a system. And patients are also freed from the hustle as they do not need to go and visit the doctor over and over again. The system is designed in such a way that it can look after the particular needs of a typical hospital or a diagnostic center and is able to provide easy and efficient storage of information related to patients.